Regional conservation status of scleractinian coral biodiversity in the republic of the marshall islands - Richards, Zoe; Beger, M. (M D P I AG, 2013)
Preventing the loss of biodiversity is a major challenge in mega-diverse ecosystems such as coral reefs where there is a critical shortage of baseline demographic data. Threatened species assessments play a valuable role in guiding conservation action to manage and mitigate biodiversity loss, but they must be undertaken with precise information at an appropriate spatial scale to provide accurate classifications. Here we explore the regional conservation status of scleractinian corals on isolated Pacific Ocean atolls in the Republic of the Marshall Islands. We compile an integrated regional species list based upon new and historical records, and compare how well the regional threat classifications reflect species level priorities at a global scale. A similar proportion of the 240 species of hard coral recorded in the current survey are classified as Vulnerable at the regional scale as the global scale using the International Union for the Conservation of Nature (IUCN) Red List criteria (23% and 20% respectively), however there are distinct differences in the composition of species. When local abundance data is taken into account, a far greater proportion of the regional diversity (up to 80%) may face an elevated risk of local extinction. These results suggest coral communities on isolated Pacific coral reefs, which are often predicted to be at low risk, are still vulnerable due to the small and fragmented nature of their populations. This reinforces that to adequately protect biodiversity, ongoing threatened species monitoring and the documentation of species-level changes in abundance and distribution is imperative. © 2013 by the authors; licensee MDPI, Basel, Switzerland.